Flocculation characteristics of suspended Mississippi River mud under variable turbulence, water and salt sources, and salinity: a laboratory study - Abolfazli, Ehsan; Osborn, Ryan; Dunne, Kieran B. J.; Nittrouer, Jeffrey A.; Strom, Kyle (Frontiers in Earth Science, 2024)
Muddy sediment constitutes a major fraction of the suspended sediment mass carried by the Mississippi River. Thus, adequate knowledge of the transport dynamics of suspended mud in this region is critical in devising efficient management plans for coastal Louisiana. We conducted laboratory tank experiments on the sediment suspended in the lower reaches of the Mississippi River to provide insight into the flocculation behavior of the mud. In particular, we measure how the floc size distribution responds to changing environmental factors of turbulent energy, sediment concentration, and changes in base water composition and salinity during summer and winter. We also compare observations from the tank experiments to in situ observations. Turbulence shear rate, a measure of river hydrodynamic energy, was found to be the most influential factor in determining mud floc size. All flocs produced at a given shear rate could be kept in suspension down to shear rates of approximately 20 s-1. At this shear rate, flocs on the order of 150 to 200 µm and greater can settle out. Equilibrium floc size was not found to depend on sediment concentration; flocs larger than 100 µm formed in sediment concentrations as low as 20 mgL-1. An increase in salinity generated by adding salts to river water suspensions did not increase the flocculation rate or equilibrium size. However, the addition of water collected from the Gulf of Mexico to river-water suspensions did enhance the flocculation rate and the equilibrium sizes. We speculate that the effects of Gulf of Mexico water originate from its biomatter content rather than its ion composition. Floc sizes in the mixing tanks were comparable to those from the field for similar estimated turbulent energy. Flocs were found to break within minutes under increased turbulence but can take hours to grow under conditions of reduced shear in freshwater settings. Growth was faster with the addition of Gulf of Mexico water. Overall, the experiments provide information on how suspended mud in the lower reaches of the Mississippi might respond to changes in turbulence and salinity moving from the fluvial to marine setting through natural distributary channels or man-made diversions.